Natterjack Toad makes a mighty crunch - Taylor, Sean, 1965-; Durst, Kathryn (Candlewick Press, 2025)
"It's a perfect day. The sky is blue, the water is sparkling, and Natterjack Toad has a packet of his most-favorite snack: delicious chocolate-chunk crunchy-munch cookies. He can't wait to dig in. But not so fast! A lanky heron is intruding on his hidey-hole! Natterjack Toad is off, quickety-whip. But every time he tries to eat his cookies, there's someone in the way--someone on the lookout for a (toady) snack themselves"--Provided by publisher.
Keywords: Natterjack toad -- Juvenile fiction; Toads -- Juvenile fiction; Animals -- Juvenile fiction; Cookies -- Juvenile fiction; Humorous stories; Picture books -- Juvenile fiction; Picture books